2003
DOI: 10.2216/i0031-8884-42-6-629.1
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and body scale structure of Heterocapsa ovata sp. nov. and Heterocapsa orientalis sp. nov. (Peridiniales, Dinophyceae)

Abstract: Cellular and body scale structure of Heterocapsa ovata sp. nov. and Heterocapsa orientalis sp. nov. (Peridiniales, Dinopbyceae) MITSUNORI IWATAKI'*t, LIZETH BOTEs2, TOMOHIRO SAWAGUCHI3, KATSUSHI SEKIGUCHI4 AND YASUWO FUKUyo5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 13 publications
2
36
0
Order By: Relevance
“…On the other hand, viability as Table 1. Characters of body scale ultrastructure in Heterocapsa species taken from Iwataki et al (2004) with the addition of Heterocapsa minima, H. psammophila (Tamura et al 2005), H. huensis (Iwataki et al, 2009) and H. arctica subsp. frigida (Rintala et al, 2010) free-living cells has been demonstrated for another Heterocapsa isolated from acantharia.…”
Section: Molecular Genetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, viability as Table 1. Characters of body scale ultrastructure in Heterocapsa species taken from Iwataki et al (2004) with the addition of Heterocapsa minima, H. psammophila (Tamura et al 2005), H. huensis (Iwataki et al, 2009) and H. arctica subsp. frigida (Rintala et al, 2010) free-living cells has been demonstrated for another Heterocapsa isolated from acantharia.…”
Section: Molecular Genetic Analysismentioning
confidence: 99%
“…E-mail: rafael.salas@marine.ie H. circularisquama Horiguchi is a harmful species (Nagai et al, 1996) which caused large-scale bivalve mortalities in Japan in 1992 (Matsuyama et al, 1997) and is a serious threat to the Japanese and Hong Kong mussel industry. The discovery of this species and the obvious need to discriminate it correctly and without ambiguity from other co-occurring Heterocapsa species have driven many studies on the genus Heterocapsa in Japan in the last 15 years (Horiguchi, 1995(Horiguchi, , 1997Matsuyama et al, 1997;Matsuyama, 1999;Iwataki et al, 2002aIwataki et al, , 2002bIwataki et al, , 2003Iwataki et al, , 2004Iwataki et al, , 2009Tamura et al, 2005;Iwataki, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, following the description of the harmful species H. circularisquama (Horiguchi 1995 (Horiguchi 1997, Iwataki et al 2002a, 2003, 2004, Tamura et al 2005. Based on a comparison of morphological characteristics, common characters of the genus Heterocapsa were reexamined and the generic diagnosis was emended by Iwataki & Fukuyo as: unicellular photosynthetic dinoflagellate with thecal plates arranged as Po, cp, 5Ј, 3a, 7Љ, 6c, 5s, 5ٞ, 2ЉЉ and three-dimensional triradiate body scales (Iwataki et al 2003).…”
Section: Taxonomic History Of Heterocapsamentioning
confidence: 99%
“…Based on a comparison of morphological characteristics, common characters of the genus Heterocapsa were reexamined and the generic diagnosis was emended by Iwataki & Fukuyo as: unicellular photosynthetic dinoflagellate with thecal plates arranged as Po, cp, 5Ј, 3a, 7Љ, 6c, 5s, 5ٞ, 2ЉЉ and three-dimensional triradiate body scales (Iwataki et al 2003). Iwataki et al (2004) reanalyzed body scale fine structures of reported Heterocapsa species and demonstrated the utility of scale structure for reliable species identification.…”
Section: Taxonomic History Of Heterocapsamentioning
confidence: 99%
See 1 more Smart Citation